Tecnologias Digitais na Educação Matemática: um panorama dos Grupos de Pesquisa brasileiros - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The insertion of technological resources in the school context, which was intensified with Emergency Remote Teaching, is only effective when the pedagogical issues involved in this process are considered. Because of this, it is essential to research the consequences of the use of Digital Technologies (DT) in the teaching and learning process. In Brazil, most scientific productions are developed by Research Groups (RG), whose data are stored in the Directory of Research Groups, on the Lattes platform. With that in mind, this research aims to map the Brazilian Research Groups that have lines of research on DT in Mathematics Education. This is a documentary, exploratory research with a qualitative approach. 161 Brazilian RG and 191 lines of research were cataloged, and some RG have more than one line of research on DT in Mathematics Education. Most RG (90%) belong to the Human Sciences large area, Education area or to the Exact and Earth Sciences large area, Mathematics area. The region in which the most RG studying DT in Mathematics Education were identified was the Southeast (47), where most Brazilian Higher Education Institutions are located. RG were created between 1993 and 2022, with 92% appearing after 2004, with the advent of fast internet. Of the 191 lines, those that did not have the objective field filled in were excluded, and 168 were analyzed, based on the following categories of predetermined objectives: comprehensive, evaluative, propositional, generalist and secondary objectives. Of these, 74 had the objective considered generalist or objective-medium, making it not possible to identify the research directions of RG to which these lines belong. Among the remaining 94 lines, 83 were grouped according to emerging categories in relation to the subjects studied by the RG, which were: Information Technology (28), Teacher Training (26), Virtual Learning Environments (13), Games (6), Digital Devices (5), Student Training (5), Inclusive Education (4), Computational Thinking (4), Learning Objects (3), Distance Education (3), Videos (3) and Assessment with DT (2). We show that Information Technology and Teacher Training are themes that have already been extensively explored within RG with lines of research on DT in Mathematics Education, while Inclusive Education, Computational Thinking, Learning Objects, Distance Education, Videos and Assessment with DT still demand attention from RG. The other 11 lines of research did not fit into the emerging categories of themes studied by the RG, but were analyzed in relation to the context in which DT are worked on in Mathematics Education or the theoretical orientation of the research. With the development of this research, we were able to point out the directions of Brazilian RG who study the use of DT in Mathematics Education, which can serve as a subsidy for RG who want to (re)structure their lines of research, thus contributing to the strengthening of their identities, and generating reflections about the direction of this field of research.
Keywords: Tecnologias Digitais; Educação Matemática; Grupos de Pesquisa; Linhas de Pesquisa; Objetivos de Pesquisa; Digital Technologies; Mathematical Education; Research Groups; Research Lines; Research Objectives; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA